EKSPLORASI ETNOMATEMATIKA PADA MASJID AGUNG AT-TAQWA BONDOWOSO SEBAGAI BAHAN AJAR PEMBELAJARAN MATEMATIKA - Sheema Hasenah Nurrosadha; Lady Agustina; Yoga Dwi Windy Kusuma Ningtyas (Universitas Muhammadiyah Semarang, 2021)
This research aims to identify ethnomathematics in the architecture of the Masjid Agung At-Taqwa Bondowoso which will be used as teaching materials for learning mathematics in the form of a series of stories that can be included in teaching materials in the form of learning videos. This research is qualitative research with an ethnographic approach. This research uses observation and interview methods as research data collection methods. The research subjects consisted of two observers and one resource person, namely the takmir of the Masjid Agung At-Taqwa Bondowoso. The results of the study show that (1) there is a mathematical concept contained in the architecture of the Masjid Agung At-Taqwa Bondowoso (2) the implementation of the two ethnomathematical aspects can be developed into a series of stories that can be contained in a teaching material in the form of learning videos.